2022
DOI: 10.3390/genes13071237
|View full text |Cite
|
Sign up to set email alerts
|

Association of TNF–α rs1800629 with Adult Acute B-Cell Lymphoblastic Leukemia

Abstract: TNF–α influences lymphomagenesis by upregulating proinflammatory and antiapoptotic pathways. In this study, we evaluated the frequency of TNF–α rs1800629 (–308 G>A) polymorphism in newly diagnosed adult patients with acute lymphoblastic leukemia (ALL) and its correlation with age at diagnosis, gender and subtype of ALL. In this case control study, a total of 330 individuals were recruited, including 165 newly diagnosed adult patients with ALL, from the Radiation and Isotope Center in Khartoum (RICK) and 165… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, the study observed a significant reduction in the serum TNF-α level in patients with acute leukemia with the start of chemotherapy [84]. A previous study on polymorphic variation of TNF-α rs1800629 (-308 G>A) in leukemia demonstrated that the frequency of the rs1800629 GA genotype was high in the patient group as compared to healthy controls and it was associated with high risk of adult B-ALL [85]. Similarly, another study found statistically significant associations of TNF-α rs1800629 SNP in AML subtypes with a higher frequency of variant genotypes in AML de novo cases [86].…”
Section: Discussionmentioning
confidence: 80%
“…However, the study observed a significant reduction in the serum TNF-α level in patients with acute leukemia with the start of chemotherapy [84]. A previous study on polymorphic variation of TNF-α rs1800629 (-308 G>A) in leukemia demonstrated that the frequency of the rs1800629 GA genotype was high in the patient group as compared to healthy controls and it was associated with high risk of adult B-ALL [85]. Similarly, another study found statistically significant associations of TNF-α rs1800629 SNP in AML subtypes with a higher frequency of variant genotypes in AML de novo cases [86].…”
Section: Discussionmentioning
confidence: 80%
“…The polymorphism of the TNF-α (−857) C/T TT genotype ‘higher expressers’ was associated with the risk of AML leukemogenesis [ 63 ]. Other studies focusing on the TNF-α rs1800629 SNP (−308G/A) have revealed that the G/G ‘low expresser’ genotype was associated with a high risk of adult B-ALL in Sudanese patients, while the −308G/A polymorphism was linked to SLE [ 64 , 65 ] and AML mortality [ 66 ]. In our study, 48 out of 51 patients (94.1%) exhibited the G/G genotype.…”
Section: Discussionmentioning
confidence: 99%
“…We found a strong association of heterozygous genotypes with elevated Lymph, Er, and CRP levels. Recently, its heterozygous genotype was found to be associated with lymphoblastic leukemia [ 34 ]. Published studies revealed a direct association between rs1800629 and premature aging due to TNF-α synthesis defect [ 35 ], which is probably related to a lack of collagen turnover [ 17 ].…”
Section: Discussionmentioning
confidence: 99%